Exploring The Ellen Show Videos to Promote The Students’ Vocabulary Learning and Engagement - Sianna, Sianna; Patahuddin, Patahuddin; Wahyuddin, Wahyuddin; Muin, Nur Azizah (Sublim: Jurnal Pendidikan, 2023)
This study investigated the effectiveness of using The Ellen Show videos to improve students' vocabulary mastery. The study was conducted with students at UPT SMK Negeri 7 Pinrang. The students were given a pre-test and post-test to measure their vocabulary mastery. The results of the post-test showed that students' vocabulary mastery improved significantly after using The Ellen Show videos. The mean score on the post-test (72.66) was significantly higher than the mean score on the pre-test (49.69, p < 0.001). These results suggest that using The Ellen Show videos can be an effective way to improve students' vocabulary mastery. There are several reasons why The Ellen Show videos may be effective for improving vocabulary mastery. First, the videos are engaging and motivating, which can help to increase students' interest in learning. Second, the videos expose students to a wide range of vocabulary words in a variety of contexts. Third, the videos can help students to practice emphasis and intonation, which can improve their fluency. Overall, the findings of this study suggest that The Ellen Show videos can be a valuable tool for teaching and learning vocabulary.